PENGEMBANGAN LKS BERBASIS SAINS TEKNOLOGI MASYARAKAT PADA KONSEP KALOR DAN PRINSIP KONSERVASI ENERGI UNTUK PEMBELAJARAN SISWA KELAS X SEMESTER 2 SMAN 4 PARIAMAN - Winda Septian Dini (PILLAR OF PHYSICS EDUCATION, 2013)
One form of the problems faced by students while studying physics matter is the lack of ability of students to associate with the subject matter of technology and society. To overcome these problems, researcher made the form of teaching materials Student Worksheet based on the concept of Science Technology Society of heat and energy conservation principles. Type of research done including the type of Research and Development (R & D). The collection instruments used in the study is the validity of the sheet according to expert staffs, the practicalities of test pieces according to physics teachers, the practicalities of test sheet according to students, test effectiveness by student learning outcomes in the cognitive, affective and psychomotor. Products and data analysis techniques are described techniques, methods graphic, descriptive statistical analysis, and comparative analysis correlated. Data analysis show two results. First, it has been successfully created worksheets science technology-based society with an attractive design worksheets. Second, Student Worksheet made ​​valid, practical and effective use in teaching physics, in addition, the worksheet can improve student learning outcomes.   Keywords : Student worksheet, STM, learning outcomes